Transforming societies after political violence : truth, reconciliation, and mental health - Hamber, Brandon (Peace psychology book series / series editor Daniel J. Christie, 2009)
(from the cover) It is a momentous day for a nation when war is over or a brutal regime ends. For victims and survivors of political atrocities, it is also a time to process trauma, to anticipate the future, to be heard-and to be healed. Transforming Societies after Political Violence offers a template for those tasked with providing truth, justice, reconciliation, and healing. This interdisciplinary study identifies complex relationships between recovery from political violence and the psychological processes that accompany widespread social change, showing how these can be integrated to strengthen both individual and society. Author Brandon Hamber draws on his extensive experience in South Africa and comparative examples from elsewhere to examine the centrality of mental health issues in transitional justice, and the social, cultural, and identity issues involved in meeting the needs of victims. In discussing reparations (what the author terms "repairing the irreparable"), the power of ambivalence, and especially concepts of closure, he eloquently sets out professionals' roles in helping survivors move beyond the toxic past without covering it up or becoming mired in it. A work that holds profound insight into the meaning of "doing justice," Transforming Societies after Political Violence is required reading for social and peace psychologists, as well as students and researchers of conflict and peace studies, transitional justice, and intergroup and international relations.